Impact of Cigarette Smoking on the Risk of Osteoporosis in Inflammatory Bowel Diseases - Ratajczak, Alicja Ewa (J Clin Med, 2021)
Cigarette smoking constitutes one of the most important modifiable factors of osteoporosis, as well as contributes to an early death, tumors, and numerous chronic diseases. The group with an increased risk of a lower bone mineral density are patients suffering from inflammatory bowel diseases. In fact, tobacco smoke, which contains more than 7000 chemical compounds, affects bone mineral density (BMD) both directly and indirectly, as it has an impact on the RANK-RANKL-OPG pathway, intestinal microbiota composition, and calcium–phosphate balance. Constant cigarette use interferes with the production of protective mucus and inhibits the repair processes in the intestinal mucus. Nicotine as well as the other compounds of the cigarette smoke are important risk factors of the inflammatory bowel disease and osteoporosis. Additionally, cigarette smoking may decrease BMD in the IBD patients. Interestingly, it affects patients with Crohn’s disease and ulcerative colitis in different ways—on the one hand it protects against ulcerative colitis, whereas on the other it increases the risk of Crohn’s disease development. Nevertheless, all patients should be encouraged to cease smoking in order to decrease the risk of developing other disorders.